(3OjhGf GHf GdfHjgs - (3GHf GdfHjg , Ydj Hf eMeO Hf GdMSf Hf jhSa, ceGd GdOjf CHh GdMSf,J (B619 (3g` s
(3ChdgG (B:s
(3bGd jeOM GdfGUQ dOjf Gddg(B: (3HZOGO ecfJfG hCMeO CMeO oMLhG Edi Jdc GdCeGcf hGSLOhG s
(3BNQgG (B:s
(3hGSJbHd GdYjO aj YR haj fYe aGdfGS aj cd jhe efc aj YjO gPG BNQ eG hLOfG ef TYQ GdbGVj GHf GdfHjg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3fSNI NGeSIs
(3hQO CjVkG JMJ Qbe (B2180s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B152s
Keywords: (3GdCOHs